2021
DOI: 10.1080/23322039.2021.1879716
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on poverty and living standards in Ghana: A micro-perspective

Abstract: The novel Coronavirus disease 2019 (COVID-19), which has become a global epidemic, hit Ghana on 12 March 2020 and, in less than a week, increased by over 300% with two deaths. As of 11 August 2020, Ghana had recorded over 41,000 cases with over 215 deaths. This study seeks to provide a micro-level evidence on how COVID-19 is posing a threat to some of the Sustainable Development Goals, particularly poverty in Ghana. Specifically, the study examined the effect of COVID-19 on poverty and living standards of Ghan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…Moreover, the investigation of the most impacted persons by the pandemic. Bukari et al ( 2021 ), for example, concluded that the pandemic had significantly deteriorated standards of living, increased poverty rates, and impacted mostly female class in Ghana. A major issue of interest that arose in association with COVID-19 pandemic is the need to better coordinate the efforts of global health actors to attain health-related SDGs (Spicer et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the investigation of the most impacted persons by the pandemic. Bukari et al ( 2021 ), for example, concluded that the pandemic had significantly deteriorated standards of living, increased poverty rates, and impacted mostly female class in Ghana. A major issue of interest that arose in association with COVID-19 pandemic is the need to better coordinate the efforts of global health actors to attain health-related SDGs (Spicer et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The epidemic resulted in the economic growth in the first quarter of 2020 is -6.8%, and 2.3% in the whole year of 2020, which was far lower than that of 2019 (6.0%) [25]. The containment measures, such as the lockdowns, quarantine measures and social distancing, contributed to protect people from infecting the disease but disrupted the livelihoods of millions of populations [26]. The economic burden of these strict control measures is remarkably heavy [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent estimates, 3 billion people throughout the world do not have access to soap or water at home, 900 million children do not have access to soap and water at school, and up to 40% of health care institutions lack hand hygiene equipment [36]. On average, according to our analysis, the proportion of the population in Africa with access to water and soap hand-washing facilities is 35% (95% CI: [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that in the absence of intervention, peak infection caseloads are maximized, but there are no variations in infection levels between poor and non-poor people. Another study by Chie et al investigated the effect of COVID-19 on poverty and living standards in Ghana [43]. The study went on to look at which groups of people within the income distributions were the worst impacted by the epidemic.…”
Section: Discussionmentioning
confidence: 99%